Inhibition of non-small cell lung cancer (NSCLC) proliferation through targeting G6PD - Chanda,Makamas; Anuntasomboon,Pornchai; Ruangritchankul,Komkrit; Cheepsunthorn,Poonlarp; Cheepsunthorn,Chalisa L. (PeerJ, 2023)
Background Mounting evidence has linked cancer metabolic reprogramming with altered redox homeostasis. The pentose phosphate pathway (PPP) is one of the key metabolism-related pathways that has been enhanced to promote cancer growth. The glucose 6-phosphate dehydrogenase (G6PD) of this pathway generates reduced nicotinamide adenine dinucleotide phosphate (NADPH), which is essential for controlling cellular redox homeostasis. Objective This research aimed to investigate the growth-promoting effects of G6PD in non-small cell lung cancer (NSCLC). Methods Clinical characteristics and G6PD expression levels in lung tissues of 64 patients diagnosed with lung cancer at the King Chulalongkorn Memorial Hospital (Bangkok, Thailand) during 2009-2014 were analyzed. G6PD activity in NSCLC cell lines, including NCI-H1975 and NCI-H292, was experimentally inhibited using DHEA and siG6PD to study cancer cell proliferation and migration. Results The positive expression of G6PD in NSCLC tissues was detected by immunohistochemical staining and was found to be associated with squamous cells. G6PD expression levels and activity also coincided with the proliferation rate of NSCLC cell lines. Suppression of G6PD-induced apoptosis in NSCLC cell lines by increasing Bax/Bcl-2 ratio expression. The addition of D-(-)-ribose, which is an end-product of the PPP, increased the survival of G6PD-deficient NSCLC cell lines. Conclusion Collectively, these findings demonstrated that G6PD might play an important role in the carcinogenesis of NSCLC. Inhibition of G6PD might provide a therapeutic strategy for the treatment of NSCLC.
Keywords: PPP; Metabolic reprogramming; Lung cancer; NSCLC; DHEA; siG6PD; Pentose phosphate pathway; Glucose 6-phosphate dehydrogenase; Non-small cell lung cancer; Squamous cells